El uso de los cuentos infantiles para fomentar la creatividad de las niñas y niños de 4-5 años de edad del centro educativo Graciela Atarihuana de Cueva de la ciudad de Loja Periodo 2014-2015 - Torres Bermeo, Alex Mauricio (2016)
This research work was based to the use of children’ stories to encourage creativity in children between 4-5 years old at “Graciela Atarihuana de Cueva” school of Loja city 2014-2015 period. It investigation had as a general objective to analyze the use of children' stories to encourage creativity of children 4-5 years old. The methodology used in this research work were descriptive and correlational, the methods used were scientific, deductive, inductive, synthetic, descriptive, inductive, deductive, statistical. The technique used was participant observation, and as instrument the researcher applied a survey to the teachers and a Torrance test to the children. This researcher was applied with a population of 3 teachers and 23 children. Based on the results obtained with the application of creativity test from Torrance the researcher concluded that 65% of children had high creativity, while 31% of children had an average high creativity and 4% with a low average creativity, in that way the researcher could determine the effectiveness of children' stories had in the development of creativity as a teaching strategy